Niewerbalne elementy aktów mowy - Jarmołowicz, Ewa (Investigationes Linguisticae, 2005)
The purpose of the article is an attempt to more widely perceive speech acts which are usually associated only with the category of verbal behaviour. The article is a supplement to J.L. Austin’s Speech Act Theory. It is an extension of his theory of the study of nonverbal aspects of the speech act. The aim of the article is to demonstrate that the speech act is realized not only by speech but also by nonverbal elements which express, or coexpress with words, the speaker’s intentions. The examples of communication situations presented in the article serve to indicate the important function and permanent presence of the nonverbal dimension of the speech act, thereby showing that the nonverbal aspect should not be avoided when analysing speech acts or discussing theory.